ROLE OF TRACE ELEMENTS (ZN, CU, MG) IN THE POSTOPERATIVE HEALING PROCESS AFTER UROLOGICAL SURGERIES - Boborakhimov Ilhom Murodullayevich; Toxtamishev Muzaffar Hikmatxujayevich (Scholar Express Journals, 2025)
The healing process after urological surgeries is based on complex biological mechanisms and is closely dependent on the adequate supply of trace elements. In particular, zinc (Zn), copper (Cu), and magnesium (Mg) play a key role in regeneration by stimulating collagen synthesis, enhancing immune responses, and supporting the antioxidant defense system. This article analyzes the effects of these elements on postoperative wound healing, based on clinical and experimental studies. The findings suggest that monitoring trace element levels and using them as adjunctive therapy could improve recovery outcomes and reduce postoperative complications in urological practice
Keywords: Urological surgery; healing process; trace elements